Analisis Diferensiasi Materi Pendidikan Agama Islam pada Model Project Based Learning Menggunakan Pendekatan Etnografi - T. Idris; Ramli, Syahrur; Susrizal, Silvia; Zakia, Nadia; Delvica, Ghusti (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2025)
Differentiated learning has problem to serach materials. Teachers have more difficulties to get sourches. This study aims to analyze the differentiation of PAI materials using Project Based Learning model. PAI materials in high school are spread in the dimensions of Al-Qur'an Hadith, Aqidah Akhlak, Fiqh and SKI. The PjBL model is difficult for PAI teachers, especially to formulating their learning themes and activities. The researcher analyzed that the Keminangkabauan ethnographic theme can be used as the theme of PjBL. Teachers must play an active role in finding material differentiation through values, philosophies, artifacts and Minangkabau’s figures that are relevant to all dimensions of PAI. This research is a qualitative descriptive by analyzing the phenomenon of low understanding of Keminangkabauan for students in high school. This research is located at SMAN 1 Lintau, Tanah Datar Regency. The respondents of this study were 158 students and 4 PAI teachers. Primary data was obtained through interviews and analysis of teacher teaching module documents. Data triangulation was carried out by exploring in-depth aspects of material differentiation, identifying the ethnographic value of Keminangkabauan and presenting it in the form of research findings. The results of this study describe the differentiation of Keminangkabauan ethnographic material on the PAI element. The aspects used are Minangkabau proverbs which are analyzed for their relevance to PAI values, the diversity of Minangkabau cultural heritage and the analysis of classic and modern Minangkabau figures. These three ethnographic aspects are integrated with PAI material so as to produce material differentiation